Slip theory-based numerical investigation of the fluid transport behavior on a surface with a biomimetic microstructure - Jiaxin Wang; Wenxing Ma; Xiaomei Li; Weiyang Bu; Chunbao Liu (Engineering Applications of Computational Fluid Mechanics, 2019)
This paper presented a numerical simulation of drag reduction on a superhydrophobic surface with a groove structure. The computational fluid dynamics (CFD) method was used to analyze the effect of the groove microstructure when droplets impacted a superhydrophobic surface. The simulation results revealed three main characteristics: (1) The distance the droplet spread was larger along the direction parallel to the groove and smaller perpendicular to the groove; (2) Two protruding small spheres were formed at the edge of the droplet along the groove direction; (3) During retraction, the droplets presented a narrow, cross-shaped morphology. The effect of the groove structure in the two-dimensional microchannel on drag reduction near the wall was analyzed based on slip theory by the coupled level set/volume of fluid (CLSVOF) method. The air in the superhydrophobic pit formed a low-velocity vortex, which made the fluid roll on the air surface. The rolling on the surface produced a velocity slip at the gas–liquid interface. In addition, the superhydrophobic surface had an obvious drag reduction effect in the laminar flow state, but the drag reduction effect in the turbulent state was not ideal and even increased the flow resistance at the wall.